Media hegemony, activism and identity: Muslim women re-presenting Muslim women - Aly, Anne (Cambridge Scholars Press, 2009)
This chapter examines how Muslim women activate their agency in the media communication process by disengaging with the dominant messages in the media discourse that present them as subordinate and passive, an enigma shrouded in the black veil of religious oppression and constructing new narratives of belonging that define their identity in ways that oppose the hegemonic code. It reports on the findings of a qualitative research project that explored the responses to the media discourse on terrorism among Australian Muslims and the broader Australian community.